Organizational Commitment Relationship And Work Motivation With The Performance Of The Implementing Nurse At Porsea Regional General Hospital - Tumpal Manurung; Dosmaida Nababan; Veronica Patrysia Silalahi (CV. AFDIFAL MAJU BERKAH, 2023)
Organizational commitment and motivation are the determinants of the success of a defined goal. Organizational commitment and motivation also contribute to performance. Highly committed and motivated nurses will work optimally for improved performance results. Improved care performance is absolutely done to improve the image of the services provided by the hospital. The objective of the research was to find out the correlation of organizational commitment and work motivation with the performance of nurse practitioners. The research used quantitative method with cross sectional design. The samples were 116 nurse practitioners as the respondents, taken by using total sampling technique. The result of Spearman’s rho correlation test showed that there was significant correlation of organizational commitment with the performance of nurse practitioners at p-value = 0,00 < 0,05 and there was significant correlation of work motivation with the performance of nurse practitioners at p-value = 0,00 < 0,05. The result of univariate analysis shows that most of the nurses have good organizational commitment with good category 58,6%, work motivation with good category equal to 57,8% and good category performance equal to 61,2%. The result of the research showed that there was positive and significant correlation of organizational commitment and work motivation with the performance of nurse practitioners. It is expected that in the future nurses and hospitals will be more aware of how important it is to maintain commitment and motivation that are very influential towards better performance improvement.